2021
DOI: 10.21203/rs.3.rs-39219/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The climate change mitigation effects of daily active travel in cities

Abstract: Active travel (walking or cycling for transport) is considered the most sustainable form of personal transport. Yet its net effects on mobility-related CO2 emissions are complex and under-researched. Here we collected travel activity data in seven European cities and derived life cycle CO2 emissions across modes and purposes. Daily mobility-related life cycle CO2 emissions were 3.2 kgCO2 per person, with car travel contributing 70% and cycling 1%. Cyclists had 84% lower life cycle CO2 emissions than non-cyclis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…For example, longitudinal data support that 9–18-year-old active commuters have higher levels of physical activity during young adulthood and can maintain these behaviours for up to 12 years,59 thus targeted and gamified early-years interventions may be prudent prevention strategies. Other potential benefits of regular active travel, or targeted interventions, include the improved emotional health and happiness of both adolescents and adults,60 improvements in cardiovascular health (eg, exercise capacity, maximal power, blood pressure and blood parameters) in adults61–63 and adolescents64 65 and cleaner and less congested neigbourhoods66 67—all points which future intervention studies could also evaluate alongside the findings (eg, articulated decision-making processes) of our ARRIVE study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, longitudinal data support that 9–18-year-old active commuters have higher levels of physical activity during young adulthood and can maintain these behaviours for up to 12 years,59 thus targeted and gamified early-years interventions may be prudent prevention strategies. Other potential benefits of regular active travel, or targeted interventions, include the improved emotional health and happiness of both adolescents and adults,60 improvements in cardiovascular health (eg, exercise capacity, maximal power, blood pressure and blood parameters) in adults61–63 and adolescents64 65 and cleaner and less congested neigbourhoods66 67—all points which future intervention studies could also evaluate alongside the findings (eg, articulated decision-making processes) of our ARRIVE study.…”
Section: Discussionmentioning
confidence: 99%
“…A study that attempted to account for full life cycle carbon emissions, estimated CO 2 emissions per trip were 30-fold higher for an internal combustion engine car than a bicycle. 15 Shifting to a battery electric vehicle cut the car costs by two thirds, but emissions were still ten times greater than for the bike. A longitudinal study of travel patterns and personal carbon footprints found that people who cycled every day had 84% lower travel emissions than those who did not, due to less polluting trips, fewer trips overall, and shorter journeys.…”
Section: Restoring Children's Independent Active Mobility As Climate Actionmentioning
confidence: 99%
“…A longitudinal study of travel patterns and personal carbon footprints found that people who cycled every day had 84% lower travel emissions than those who did not, due to less polluting trips, fewer trips overall, and shorter journeys. 15 As well as helping to prevent climate change, increasing children's independent active mobility can also help communities to adapt to the pressures caused by climate change. Children's independent mobility has traditionally played a particularly important role in the building and maintenance of neighbourhood social capital: our networks and relationships, as well as sense of belonging.…”
Section: Restoring Children's Independent Active Mobility As Climate Actionmentioning
confidence: 99%
“…Thus, if 10% of the population were to change their travel behaviour, the emissions savings would be around 4% of life-cycle carbon dioxide emissions from all car travel. 8 Cycling is a reliable, convenient, and efficient form of transportation. In Canada, the percentage of bicycle commuter trips varies from 1% to 3%, 9 while in Europe, cities with extensive cycling infrastructure reach levels of 40%.…”
Section: Editor's Key Pointsmentioning
confidence: 99%